PHYSICOCHEMICAL PROPERTIES AND MEDICAL SIGNIFICANCE OF ALANINE - Sadullayeva Gulmira Gaybullayevna (Ustozlar uchun, 2025)
Alanine is a non-essential amino acid that plays a vital role in protein biosynthesis and energy metabolism. It exists in two forms: L-alanine and D-alanine. While L-alanine is predominantly found in proteins and living organisms, D-alanine is mostly present in bacterial cell walls. Understanding the physicochemical characteristics and medical implications of alanine is crucial in biochemistry, pharmacology, and clinical diagnostics. In this paper, we aim to analyze the physicochemical properties of alanine and explore its multifaceted role in the medical field, including its diagnostic use and therapeutic potential